Janus v AFSCME, Council 31: Judges Will Haunt You in the Second Gilded Age / Janus v AFSCME, Conseil 31: Les juges viendront vous hanter dans ce second Âge d’or - Herbert, William (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2019)
This essay examines the United States Supreme Court’s 2018 decision in Janus v AFSCME, Council 31, which concluded that agency shop provisions violate the First Amendment rights of public sector workers who are not union members but receive the fruits of the representation. This decision reversed over 40 years of precedent and imposed “right to work” as a new federal constitutional mandate, fulfilling the dream of anti-union forces since the first Gilded Age.The essay begins with a brief history of the open shop movement and the development of the agency shop as a constitutionally permissible form of union security in the private and public sectors. It then describes how an activist Supreme Court majority undermined the constitutionality of the agency shop, which set the stage for the Janus decision. The essay summarizes the majority and dissenting opinions in Janus, and describes how unions, employers, and some state legislatures are responding to the decision’s immediate impact.